Mixed Martial Arts (MMA) no Brasil: masculinidades em disputa - Almeida, Sebastião Carlos Ferreira de (2016)
The following study consists in a sociological analysis about the production of manhood styles in the universe of Mixed Martial Arts (MMA), from an ethnographic research made with a group of physical fight practitioners in the city named Goiânia-GO. Thus, it points out to the relevance of consumption and the interference of the market in the construction of some symbolic repertoire about manhood seen as essentials and/or primordials, discussing how the subjects seize and embody such an imaginary thing amidst stress, ambivalences and disputes. The document is organized into five chapters. In the first, I talk about the questionable utilization of physical fights and martial arts as an invented tradition, as an orientalist play, in the configuration of imaginary communities. In the second, I talk about the appearance of MMA coming from the Ultimate Fighting Championship (UFC), giving focus to historical and sociological aspects that takes part in the symbolic economy in which establishes some manly speeches that are important for involved agents with the dynamic of manhoods in question. The third chapter brings thoughts about implied codes to the expression of manhoods in the universe of fighters where it was realized the field research, emphasizing the usage of signs associated to the genre relations with the production of relevant styles of the habitus of fighters. I develop discussions about the acceptance of the speech of order and the discipline of the contributors in the fourth chapter, in order to determine how interactions with women and other manhoods go through the influence of conservative opinion; and how much this dynamic is responsible for the creation of conflicts in this universe. The fifth chapter talks about the biographies of iconic fighters in several levels of the field topology embodied by fighters and referees that take part of the cultural goods market around MMA and UFC. So I posit that the fight that brought the thoughts about manhoods in this study highlights the stress around the sexuality, of questions related to family and to work; and before it means a sportivization, it indicates an intense civilizing process, as it allows the fruition an uncontrolled control of the emotions and makes evident tools of social control. The respect and affection of traditional institutes like family and heterosexuality, like the possibility of social ascension through MMA, require from the fighters a self-sacrifice that reinstalls in the contemporaneous scenario the perspective of the individual discipline as a resource to the success. This process allow us to imply that dynamics and rhetoric of market (re)products styles of manhoods seen as “non corruptible” by the present day, such elements being appropriate by interested agents in the symbolic capital that is inherent in the form of disputes for hegemony. Keywords: Mixed Martial Arts, manhoods; uncontrolled control; imaginary communities; market of symbolic goods.